2021
DOI: 10.3389/fpsyg.2021.562269
|View full text |Cite
|
Sign up to set email alerts
|

Pretending to Be Better Than They Are? Emotional Manipulation in Imprisoned Fraudsters

Abstract: Fraud can cause severe financial losses and affect the physical and mental health of victims. This study aimed to explore the manipulative characteristics of fraudsters and their relationship with other psychological variables. Thirty-four fraudsters were selected from a medium-security prison in China, and thirty-one healthy participants were recruited online. Both groups completed an emotional face-recognition task and self-report measures assaying emotional manipulation, psychopathy, emotion recognition, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Public disclosure of rule violations likely jeopardizes an organization's legitimacy, hinders its resource acquisition, and reduces stakeholder confidence (Deephouse, 1999). Several studies have shown that Chinese firms that were punished for illegitimate activities suffer from legitimacy discount in the public (Wang, 2010;Wang, Liu, et al, 2021;Zhang, Xu, Chen, & Jing, 2020), while culpable leaders (executives and directors) can also be stigmatized or dismissed (Conyon & He, 2016;Firth et al, 2011;Firth, Wong, Xin, & Yick, 2016). Therefore, to maintain regulators' good faith, culpable leaders are strongly motivated to conceal information in order to protect their jobs, reputations, or other personal (or small group) interests (Gundeep, 2017).…”
Section: Compartmentalization In Governance Positions and Regulatory ...mentioning
confidence: 99%
“…Public disclosure of rule violations likely jeopardizes an organization's legitimacy, hinders its resource acquisition, and reduces stakeholder confidence (Deephouse, 1999). Several studies have shown that Chinese firms that were punished for illegitimate activities suffer from legitimacy discount in the public (Wang, 2010;Wang, Liu, et al, 2021;Zhang, Xu, Chen, & Jing, 2020), while culpable leaders (executives and directors) can also be stigmatized or dismissed (Conyon & He, 2016;Firth et al, 2011;Firth, Wong, Xin, & Yick, 2016). Therefore, to maintain regulators' good faith, culpable leaders are strongly motivated to conceal information in order to protect their jobs, reputations, or other personal (or small group) interests (Gundeep, 2017).…”
Section: Compartmentalization In Governance Positions and Regulatory ...mentioning
confidence: 99%